MEUSARE TEUMULEH: Pelatihan Ortografi Bahasa Aceh Berbasis Kearifan Lokal Hadih Maja - Nurlayli Yanti; Inas Ghina; Humaira Anwar (Ilin Institute, 2026)
The Acehnese language constitutes an essential element in the formation of cultural identity, transmitted across generations. However, the ability of the younger generation to write in Acehnese in accordance with orthographic conventions has shown a declining trend. The Meusare Teumuleh program was implemented at Madrasah Aliyah Negeri (MAN) 5 Aceh Besar as a revitalization effort through training based on the local wisdom of Hadih Maja, particularly in the absence of formal Acehnese language instruction at the institution. The implementation methods included socialization, material development, training, mentoring, and evaluation through pre-tests and post-tests. The results indicated a significant improvement in students’ competencies, with scores increasing from an initial range of 10–20 to 45–75. The program not only enhanced students’ understanding of Acehnese orthographic systems but also fostered awareness of local cultural values, while encouraging the sustainability of culture-based learning within the school environment.